The Rainfall Sensitivity of Tropical Net Primary Production in CMIP5 Twentieth- and Twenty-First-Century Simulations - Negrón-Juárez, Robinson I.; Riley, William J.; Koven, Charles D.; Knox, Ryan G.; Taylor, Philip G.; Chambers, Jeffrey Q. (Journal of climate, 2015)
In this study, the authors used the relationship between mean annual rainfall (MAR) and net primary production (NPP) (MAR–NPP) observed in tropical forests to evaluate the performance (twentieth century) and predictions (twenty-first century) of tropical NPP from 10 earth system models(ESMs) from phase 5 of the Coupled Model Intercomparison Project (CMIP5). Over the tropical forest domain most of the CMIP5 models showed a positive correlation between NPP and MAR similar to observations. The GFDL, CESM1, CCSM4, and Beijing Normal University (BNU) models better represented the observed MAR–NPP relationship. Compared with observations, the models were able to reproduce the seasonality of rainfall over areas with long dry seasons, but NPP seasonality was difficult to evaluate given the limited observations. From 2006 to 2100, for representative concentration pathway 8.5 (RCP8.5) (and most RCP4.5 simulations) all models projected increases in NPP, but these increases occurred at different rates. By the end of the twenty-first century the models with better performance against observed NPP–MAR projected increases in NPP between ∼2% (RCP4.5) and ∼19% (RCP8.5) relative to contemporary observations, representing increases of ∼9% and ∼25% relative to their historical simulations. When climate and CO₂ fertilization are considered as separate controls on plant physiology, the current climate yields maximum productivity. However, as future climate changes become detrimental to productivity, CO₂ fertilization becomes the dominant response, resulting in an overall increase in NPP toward the end of the twenty-first century. Thus, the way in which models represent CO₂ fertilization affects their performance. Further studies addressing the individual and simultaneous effect of other climate variables on NPP are needed.